Autism Knowledge, Perceptions of Potential Outcomes and Attitudes About Autism Education in Greece - Despina Papoudi; Katerina Antonopoulou (Education Sciences)
The present study examines professionals’ knowledge of autism as well as perceptions of potential outcomes and attitudes about education and the inclusion of autistic children in Greece. One hundred and eighty mainstream school teachers, special needs teachers and health/social care professionals, all working in the education sector, responded to self-reported questionnaires. Results showed between-group differences in the knowledge of autism prognosis and in self-efficacy in supporting autistic children, with health/social care professionals outperforming teachers. Mainstream school teachers, however, achieved higher scores compared to health/social care professionals in their perceptions of life and literacy outcomes and in their attitudes about the use of modified assessment methods for autistic children. The present findings support the need for improving perceptions for autistic children, promoting inclusive practices and a multi-disciplinary shared understanding of autism among professionals within the education sector and beyond.